The Effect of Social Outreach on Financial Performance of Microfinance Institutions in Bangladesh - Rizkiah, Siti Kholifatul (International Journal of Economics, Management and Accounting, 2019)
Microfinance institutions (MFIs) were first initiated to solve poverty problems by extending credit to poor communities. The emphasis on financial performance has created a concern that MFIs would be having a mission drift and be driven away from their social mission to serve the poor. This study examines the impact of breadth and depth of social outreach on the financial performance of 434 MFIs in Bangladesh in 2015 using The Ordinary Least Squares (OLS) regression method. The findings show a significant positive relationship between the breadth of social outreach and financial performance. On the contrary, it is found that the depth of outreach has a negative significant impact on MFI financial performance. This finding confirms the notion that MFI is not supposed to be commercially driven and it is more suitable to run MFI as a non-profit. This study offers analysis of both depth and breadth of outreach in a specific developing country to give an insight into how the focus on social outreach would impact the financial performance of MFI in the poverty prevalent environment.